Pericles Should Learn to Fix a Leaky Pipe – Why Trial Advocacy Should Become Part of the LLB Curriculum (Part 1) - Gravett, Willem Hendrik (Potchefstroom Electronic Law Journal, 2018)
It is a sad fact that at most university law schools in South Africa, a student can graduate without ever having set foot in a courtroom, and without ever having spoken to, or on behalf of, a person in need of advice or counsel. The past several years have witnessed a swelling chorus of complaints that the current LLB curriculum produces law graduates who were "out of their depth" in practice. My purpose is to make a case for the inclusion in the LLB curriculum of a course in trial advocacy. This endeavour of necessity invokes the broader debate over the educational objectives of a university law school – a debate memorably framed by William Twining as the two polar images of "Pericles and the plumber". My thesis is that the education of practising lawyers should be the primary mission of the university law school. The first part of this contribution is a response to those legal academics who hold that the role of the law school is to educate law students in the theories and substance of the law; that it is not to function as a trade school or a nursery school for legal practice. With reference to the development of legal education in the United States, I argue that the "education/training" dichotomy has been exposed as a red herring. This so-called antithesis is false, because it assumes that a vocational approach is necessarily incompatible with such values as free inquiry, intellectual rigour, independence of thought, and breadth of perspective. The modern American law school has shown that such so-called incompatibility is the product of intellectual snobbery and devoid of any substance. It is also often said that the raison d’être of a university legal education is to develop in the law student the ability "to think like a lawyer". However, what legal academics usually mean by "thinking like a lawyer" is the development of a limited subset of the skills that are of crucial importance in practising law: one fundamental cognitive skill – analysis – and one fundamental applied skill – legal research. We are not preparing our students for other, equally crucial lawyering tasks – negotiating, client counselling, witness interviewing and trial advocacy. Thinking like a lawyer is a much richer and more intricate process than merely collecting and manipulating doctrine. We cannot say that we are fulfilling our goal to teach students to "think like lawyers", because the complete lawyer "thinks" about doctrine and about trial strategy and about negotiation and about counselling.